2003
DOI: 10.2105/ajph.93.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Patterns Among Gulf War Registry Veterans

Abstract: These findings are consistent with previous investigations of symptom patterns in Gulf War veterans. This multisymptom illness may be more fully characterized by the extent, breadth, and severity of symptoms reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…9 We have labelled the three factors identified in the Gulf War and comparison group subjects in this study as psychophysiological distress, cognitive distress, and arthroneuromuscular distress. These factors display some similarity with those from each of the previous ten studies (six with a comparison group, 7-12 and four without a comparison group [13][14][15][16] ). Exact comparisons involving these studies are difficult because of the use of different symptom questionnaires.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…9 We have labelled the three factors identified in the Gulf War and comparison group subjects in this study as psychophysiological distress, cognitive distress, and arthroneuromuscular distress. These factors display some similarity with those from each of the previous ten studies (six with a comparison group, 7-12 and four without a comparison group [13][14][15][16] ). Exact comparisons involving these studies are difficult because of the use of different symptom questionnaires.…”
Section: Discussionmentioning
confidence: 52%
“…Most of these studies have included a military comparison group whose members did not deploy to the Gulf, 7-12 although four were confined to Gulf War veterans only. [13][14][15][16] Of the studies that included comparison groups, all except one found no important differences in the pattern of self-reported symptoms between the study groups. These studies did not provide evidence to support the existence of a unique syndrome among Gulf War veterans beyond the possibility that Gulf War veterans may lie at different locations on the same underlying dimensions, when compared to members of the comparison group.…”
mentioning
confidence: 96%
“…Veterans from the Korean and Vietnam conflicts are aging along with the rest of the U.S. population. Evidence of increased susceptibility to ALS and MS also exists among veterans of the first gulf war [100][101][102]. Finally, the incidence of polytrauma among veterans of Operation Iraqi Freedom and Operation Enduring Freedom is resulting in a cohort of veterans with multiple physical, cognitive, and perceptual impairments [103].…”
Section: Will Need For Smart Wheelchairs Grow?mentioning
confidence: 99%
“…Research | Article Veterans returning from the Gulf War of 1990-1991 described multiple-organ symptoms that included chemical sensitivity, chronic fatigue, fibromyalgia, neurocognitive deficits, irritable bowel syndrome, headaches, joint pains, fever, and a general unwellness, referred to as Gulf War syndrome (GWS) (Cherry et al 2001;Gray et al 2002;Haley and Kurt 1997;Hallman et al 2003;Iowa Persian Gulf Study Group 1997;Kang et al 2002;Kroenke et al 1998;Lashof and Cassells 1998). GWS probably has a multiplefactorial etiology involving possible chemical exposures (Haley and Kurt 1997).…”
mentioning
confidence: 99%